LEGAL PROTECTION AGAINST DEPOSITORS' CUSTOMERS WITH MUDHARABAH CONTRACT ON ISLAMIC BANKS - Elvira Fitriyani Pakpahan (Jurnal Pembaharuan Hukum, 2019)
Deposit type most often used by Islamic Bank in collecting funds from the public is revshare system (mudharabah) where the customer is acting as an investor and profit from business carried on by the bank. But in practice mudharabah can also loss caused by managers (Banks) in running the business. The problem in this research is how the legal protection of depositors with mudharabah in Islamic banks. With normative juridical research method and approach to literature. Results of the study stated that the legal protection of depositors in Islamic banking are protected by rules that are already fairly well from the Financial Services Authority and the Institute of deposit insurance, even the rules better than  protection applied to customers of conventional banks. LPS in Regulation 2 of 2010 Article 44 stated that the interest rate is considered reasonable set LPS does not apply in determining the status of the deposit guarantee to deposits based on Islamic principles because Islamic Bank using revshare principle in operation.